Rethinking Majors in Australian Indigenous Studies. Issue 1 (15th August 2014) - Nakata, Martin; Nakata, Vicky; Keech, Sarah; Bolt, Reuben; Barney, Katelyn; Shannon, Cindy; Nakata, Martin
<x content-type="archive" xml:space="preserve">Abstract</x> The challenges of finding more productive ways of teaching and learning in Australian Indigenous Studies have been a key focal point for the Australian Indigenous Studies Learning and Teaching Network. This article contributes to this discussion by drawing attention to new possibilities for teaching and learning practices amid the priority being given to the more practice-oriented educational approaches for future professionals and the cultural competencies of all students and staff. We explore courses sequenced as Indigenous Studies Majors and discuss two different conceptualisations for framing teaching and learning in Indigenous Studies courses — decolonising theory and cultural interface theory — and the implications for some of the teaching and learning practices they facilitate, including the positioning of students and the development of dispositions for future professional practice. We suggest that those academic teams who structure course sequences in Indigenous Studies have a role to play in experimenting with shifts in teaching and learning frameworks and the design of course sequences to encourage approaches that are more focused on developing students' breadth and depth of knowledge of the field, as well as their capacities for deeper engagements with Indigenous thought and the scholarly disciplines.